PENERAPAN LOGIKA FUZZY SUGENO UNTUK PENENTUAN REWARD PADA GAME EDUKASI AKU BISA - Chaulina Alfianti Oktavia; Rakhmad Maulidi (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2019)
This study discusses an application of fuzzy logic in educational game. This game requires a fast player response. We made this game in order to raise children awareness to encounter strangers. In this game, strangers are enemies in the form of hand drawings. The main characters in this game are boy and girl. The player can choose a character as desired. Each selected character has a different level. At each level, there is a level of difficulty based on the ease of passing enemies to reach the goal. The player would win the game once he/she manages to escape from strangers and arrives at home. Each level of the game has an enemy who tries to approach the player. If the enemy caught by the player, it will get consequences according to the fuzzy rules that applied to the game. The application of fuzzy logic in this game is to regulate the form of reward that will receive by the player. The basis for determining reward is the living conditions, time, and scores obtained by the player. In this research, we use fuzzy Sugeno logic for giving rewards. We conclude that fuzzy logic applies to our educational game.